NASIONALISME DAN MILITERISME: IDEOLOGISASI HISTORIOGRAFI BUKU TEKS PELAJARAN SEJARAH SMA - Mulyana, Agus (History Department, Semarang State University and Historian Society of Indonesia, 2013)
The Indonesian National History Lesson textbook for Senior High School is one of the works of historiography aimed for educational purposes. History as an educational tool will be influenced by the goal of education, especially the goal of history lesson, set out in the curriculum. Political base is one of the important bases in designing curriculum. The political base meant is the governmental political policy. The preparation of history materials in the Indonesian National History textbooks can not be separated from the influence of governmental political policy. One of the effects on the textbook is the existence of ideologization. The forms of ideologization that exist in the historiography of the Indonesian National History textbooks, among others, are nationalism and militarism. Key words: historiography, textbook, nationalism, militarism Ã‚Â Buku teks Pelajaran Sejarah Nasional Indonesia untuk SMA merupakan salah satu karya historiografi yang ditujukan untuk kepentingan pendidikan. Sejarah sebagai alat pendidikan akan dipengaruhi oleh tujuan pendidikan, khususnya tujuan mata pelajaran sejarah, yang tertuang dalam kurikulum. Penyusunan kurikulum memiliki salah satu landasan penting, yaitu landasan politik. Landasan politik yang dimaksud adalah kebijakan politik pemerintah. Penyusunan materi sejarah dalam buku teks Sejarah Nasional Indonesia tidak lepas dari pengaruh kebijakan politik pemerintah. Salah satu pengaruh terhadap buku teks tersebut adalah adanya ideologisasi. Bentuk ideologisasi yang ada dalam historiografi buku teks Sejarah Nasional Indonesia diantaranya adalah nasionalisme dan militerisme. Kata kunci: historiografi, buku teks, nasionalisme, militerisme